Loss of Mecp2 in Substantia Nigra Dopamine Neurons Compromises the Nigrostriatal Pathway - Gantz, Stephanie C. (Society for Neuroscience, 2011)
Mutations in the methyl-CpG-binding protein 2 (MeCP2) result in Rett syndrome (RTT), an X-linked disorder that disrupts neurodevelopment. Girls with RTT exhibit motor deficits similar to those in Parkinson's disease, suggesting defects in the nigrostriatal pathway. This study examined age-dependent changes in dopamine neurons of the substantia nigra (SN) from wild-type, presymptomatic, and symptomatic Mecp2(+/−) mice. Mecp2(+) neurons in the SN in Mecp2(+/−) mice were indistinguishable in morphology, resting conductance, and dopamine current density from neurons in wild-type mice. However, the capacitance, total dendritic length, and resting conductance of Mecp2(−) neurons were less than those of Mecp2(+) neurons as early as 4 weeks after birth, before overt symptoms. These differences were maintained throughout life. In symptomatic Mecp2(+/−) mice, the current induced by activation of D(2) dopamine autoreceptors was significantly less in Mecp2(−) neurons than in Mecp2(+) neurons, although D(2) receptor density was unaltered in Mecp2(+/−) mice. Electrochemical measurements revealed that significantly less dopamine was released after stimulation of striatum in adult Mecp2(+/−) mice compared to wild type. The decrease in size and function of Mecp2(−) neurons observed in adult Mecp2(+/−) mice was recapitulated in dopamine neurons from symptomatic Mecp2(−/y) males. These results show that mutation in Mecp2 results in cell-autonomous defects in the SN early in life and throughout adulthood. Ultimately, dysfunction in terminal dopamine release and D(2) autoreceptor-dependent currents in dopamine neurons from symptomatic females support the idea that decreased dopamine transmission due to heterogeneous Mecp2 expression contributes to the parkinsonian features of RTT in Mecp2(+/−) mice.